Efficiency of stabilized stannous fluoride in the complex prophylaxis of dental caries in young people - Політун, Антоніна Михайлівна; Марченко, Наталья Сергеевна (ScienceRise: Medical Science, 2016)
In the work were presented the results of the clinical efficiency of preparations with stabilized stannous fluoride in the complex prophylaxis of caries in young people that stipulates the use of phytopreparations “Calcid” and UncariaTomentosa extract for improvement of caries resistance of the teeth hard tissues. Aim of the work. The improvement of the efficiency of the primary prophylaxis of the dental caries in young people by prescription of the vitaminic-mineral complex and stabilized stannous fluoride for intensifying the processes of teeth enamel remineralization. Materials and methods of research: epidemiological, clinical and statistical methods of research. Results of research: In the result of combining in the prophylactic complex the methods of endo- and exogenous prophylaxis allowed significantly raise the degree of caries resistance of the teeth hard tissues that is indicated by the essential difference between the indices of the growth of the caries intensity in the group of comparison, main and control groups and also the high values of reduction attained during the year of the use of the complex of prophylactic arrangements in young people. We must specially note the efficiency of stabilized stannous fluoride in the complex prophylaxis of dental caries that is 32 % in comparison with preparations that include sodium fluoride. The research demonstrates that the state of the oral cavity hygiene in all groups of examined young people with the high intensity of caries can be assessed as unsatisfactory one. From the aforesaid data we can see, that the combination of the preparations for the oral cavity care including stannous fluoride with prophylactic vitaminic-mineral complex has the reliable prophylactic impact, favor the decrease of the caries intensity and improves the indices of the state of the oral cavity hygiene in 1,6 times. The rise of the degree of caries resistance of enamel in one year in patients of the control group (4,88±0,15) was less evident under the effect of exogenous methods of prophylaxis and reliably insignificant comparing with the initial data (4,56±0,14). The special attention must be paid to the reliable difference of the enamel resistance test between the main and control groups 4,27±0,10 and 4,88±0,15 respectively (р<0,05). Conclusions: The essential difference between the indices of growth of caries intensity in the main group (17) and the high values of reduction (68 %) with the group of comparison (32 %), and also the positive changes of structural-functional enamel resistance (from 5,32±0,13 to 4,27±0,10) attained after the year of using the offered complex of prophylactic arrangements in combinations with the preparations for the oral cavity care including stabilized stannous fluoride in young people, proved its high clinical efficiency